An Analysis of Strategies to Face Service Marketing Challenges - Legy C Joseph (International Journal of Advanced Science and Technology, 2020)
Service marketing is different from product marketing though the marketing mix of product is part of marketing mix of services. The characteristics and challenges faced for both product and service are totally different. The service sectors are so diverse, to name a few, banking, insurance, telecommunications, transportation, hotel industries and personal care services etc. Based on the characteristics and nature of the service, the challenges for each of these marketing will differ. The strategies for marketing the service should be designed to overcome the challenges faced. The current paper discusses the challenges that are being faced in service marketing and the analyses the strategies that are to be followed to face the challenges and achieve the target in the marketing..